Yield components affected by rice black-streaked dwarf virus disease in rice cultivars with different resistance levels - Sun, Yue; Jing, Dedao; Zhang, Jiayuan; Du, Linlin; Li, Chenyang; Lan, Ying; Lin, Feng; Zhou, Tong (Frontiers in Microbiology, 2023)
Rice black-streaked dwarf virus disease (RBSDVD) is one of the most destructive rice viral diseases, leading to severe yield losses in rice production. However, little is known about the yield-related components associated with the disease and no resistance cultivars have been successfully used in rice breeding. In this study, seven rice cultivars were analyzed, including six commercial rice varieties and a new line Zhongjian No. 201 (ZJ201) containing the resistance gene OsAP47. Resistance levels of these cultivars were evaluated and yield components were collected, including panicle length (PL), spikelets per panicle (SPP), ripened grains per panicle (RGPP), as well as panicles per square meter (PPSM) and 1000-grain weight (TGW). Seed setting rate (SSR) were calculated with the data of SPP and RGPP. The results showed that ZJ201 displayed the highest resistance level and most of the commercial rice cultivars exhibited susceptible to RBSDVD. Yields of all the rice cultivars were significantly declined except ZJ201 and yield losses produced by RBSDVD were mainly due to the reduction of PL, SPP, RGPP and TGW, suggesting that developments of these traits are associated with RBSDV infection. Resistant rice cultivar could reduce yield losses by maintaining normal development of the traits. Significant correlations were identified between resistance levels and the yield components except SSR and PPSM. The results provided useful clues for understanding the mechanisms of RBSDV invasion and its effect on rice production. ZJ201 was demonstrated as a resistance material that could be used in rice breeding.